Is carvedilol better than propranolol in portal hypertension? - Wong, Sook Yee; Lee, Joel; Anile Sule, Ashish (AME Medical Journal, 2017)
Liver cirrhosis is a leading cause of death worldwide. Portal hypertension remains as a major complication of liver cirrhosis. Hepatic venous pressure gradient (HVPG) measurement is the best available method to evaluate the presence and severity of portal hypertension (1). Beta blockers have been shown to reduce HVPG and thus reduce further complications, such as ascites and hepatorenal syndrome (1). Traditional non-selective beta blockers (NSBB) such as propranolol, or endoscopic variceal ligation (EVL) were considered the gold standard in the prevention of first variceal haemorrhage arising from raised portal pressures (Baveno V) (2).